Morphological and Molecular Diversity of Phytoplankton in Beibu Gulf, Northern South China Sea - Shalini Thevarajan; Pengfei Sun; Pengbin Wang; Jie Xu; Jie Chen; Yongyu Tan; Junjie Zheng; Mengmeng Tong (Ecology and Evolution, 2025)
ABSTRACT The Beibu Gulf, a vital region for marine biodiversity and aquaculture, is increasingly affected by nutrient‐driven ecological shifts in the phytoplankton community. This study combined morphology and eDNA metabarcoding (18S rDNA V4) to investigate phytoplankton diversity and environmental drivers during summer and winter in the Beibu Gulf. Metabarcoding detected 3.5 times more phytoplankton species, contributing to higher species diversity and richness than morphology. Metabarcoding identified 200 phytoplankton genera from eight phyla, while morphology only identified 49 genera from six phyla. Both methods revealed different dominant phytoplankton communities. Bacillariophyta and Haptophyta dominated the phytoplankton community based on morphology, in summer and winter, respectively; meanwhile, Dinophyta dominated in both seasons under metabarcoding due to their high 18S rDNA copy number. Altogether, 83 HAB and/or toxic species were identified, among which 10 were dominant, suggesting a high risk of HAB outbreaks in the Beibu Gulf. Phytoplankton abundance increased from south to north and west to east in both seasons, following the high input of dissolved inorganic nitrogen (DIN) and silicate. Excess ammonium input can promote the dominance of Scrippsiella trochoidea and Heterocapsa circularisquama, positioning them as emerging HAB species, while excess DIN caused extreme phosphorus limitation and favored the dominance of Phaeocystis globosa in the Beibu Gulf. This study provided a comprehensive description of the influence of environmental drivers on the phytoplankton community in the Beibu Gulf.